Effectiveness of customer social participation for academic purposes: a case of informal WhatsApp groups - A.A.I. Lakmali; Nalin Abeysekera; D.A.C. Suranga Silva (AAOU Journal, 2021)
Purpose – Customer social participation (CSP) is a new phenomenon that has emerged with the evolution of social media. Current literature designates customer participation in social media as “CSP”. Although CSP has been investigated in the online brand community context in social media, it has been little investigated in the context of student customers using WhatsApp – a highly trending social media platform among learners. Thus, this study aims to investigate the effectiveness of CSP in informal WhatsApp groups for academic purposes among undergraduate students of management studies. Design/methodology/approach – The study adopted a single cross-sectional survey design. A structured online questionnaire was employed. Using convenience sampling technique, data were collected from 170 undergraduates of the Bachelor of Management Studies programme at the Open University of Sri Lanka. Findings – The results revealed significant positive effects of functional, social and hedonic benefits with CSP. Meanwhile, the relationship between psychological benefits and CSP was insignificant. Furthermore, there is no influence of age and level of study on CSP among the learners in informal WhatsApp groups. Moreover, at present, the level of CSP in WhatsApp for academic purposes among students is moderate. Originality/value – The role of the student as the customer and student behaviour in informal WhatsApp groups established for academic purposes have been little investigated in the field of open and distance education services. In this context, this study empirically validated the model of participation benefits and CSP in WhatsApp groups informally established for academic purposes.